Environmental stress cracking performance of polyether and PDMS‐based polyurethanes in an in vitro oxidation model. Issue 6 (29th April 2016) - Gallagher, Genevieve; Padsalgikar, Ajay; Tkatchouk, Ekaterina; Jenney, Chris; Iacob, Ciprian; Runt, James
ABSTRACT: Environmental stress cracking (ESC) was replicated in vitro on Optim™ (OPT) insulation, a polydimethylsiloxane‐based polyurethane utilized clinically in cardiac leads, using a Zhao‐type oxidation model. OPT performance was compared to that of two industry standard polyether urethanes: Pellethane ® 80A (P80A), and Pellethane ® 55D (P55D). Clinically relevant specimen configurations and strain states were utilized: low‐voltage cardiac lead segments were held in a U‐shape by placing them inside of vials. To study whether aging conditions impacted ESC formation, half of the samples were subjected to a pretreatment in human plasma for 7 days at 37°C; all samples were then aged in oxidative solutions containing 0.9% NaCl, 20% H2 O2, and either 0 or 0.1 M CoCl2, with or without glass wool for 72 days at 37°C. Visual and SEM inspection revealed significant surface cracking consistent with ESC on all P80A and P55D samples. Sixteen of twenty P80A and 10/20 P55D samples also exhibited breaches. Seven of 20 OPT samples exhibited shallow surface cracking consistent with ESC. ATR–FTIR confirmed surface changes consistent with oxidation for all materials. The number average molecular weight decreased an average of 31% for OPT, 86% for P80A, and 56% for P55D samples. OPT outperformed P80A and P55D in this Zhao‐type in vitro ESC model. An aging solution of 0.9% NaCl, 20% H2 O2, and 0.1 M CoCl2, with glass wool provided the best combination of ESC replication and ease of use. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1544–1558, 2017.